Polymorphism and synergism of angiotensin-converting enzyme (ACE) and plasminogen activator inhibitor-1 (PAI-1) genes in coronary artery disease. (December 2015) - Sakhteh, Maryam; Poopak, Behzad; Amirizadeh, Naser; Shamshiri, Ahmadreza; Bagheri, Abdolhamid; Faranoush, Mohammad
Introduction: Among the genetic factors for coronary artery diseases, PAI-1 4G/5G and ACE I/D polymorphisms can be noted. This study was carried out to investigate the association of these two polymorphisms and their synergism in coronary artery disease (CAD) from a sample of the Iranian population. Materials and methods: Sixty-one patients with a history of CAD and 92 healthy controls participated in our study. After DNA extraction from leukocytes, PCR was performed to characterize PAI-1 4G/5G and ACE I/D polymorphisms, using an amplification refractory mutation system technique. Results: In the studied patients, PAI-1 polymorphisms were 24.6%, 45.9%, and 29.5% for 4G/4G, 4G/5G and 5G/5G, respectively; the values for controls were 20.7%, 42.2% and 37.0%. The distribution rates of genotypes I/I, I/D and D/D in patients accounted for 29.5%, 45.9% and 24.6%; in the control group these figures were estimated to be 40.2%, 40.2% and 19.6%. Conclusion: Single and multivariate analyses showed a significant difference for the conventional risk factors, including hypertension, diabetes, hyperlipidemia, smoking and family history, for CAD between patients and controls ( p value ≤ 0.001). However, no significant correlation was demonstrated considering ACE and PAI-1 polymorphisms either in association with 4G/4G or D/D genotypes or a combination of them in the Iranian population in the current study.